2016
DOI: 10.2739/kurumemedj.ms6300003
|View full text |Cite
|
Sign up to set email alerts
|

Primary Hinged External Fixation of Terrible Triad Injuries and Olecranon Fracture-Dislocations of the Elbow

Abstract: Summary:This study aimed to introduce a new treatment that apples primary hinged external fixation for complex fracture-dislocations of the elbow in 12 cases. We retrospectively assessed the functional outcomes of eight patients with terrible triad injuries and three patients with an olecranon fracture-dislocation of the elbow, who were treated at our hospital using a primary hinged external fixator between June 2012 and December 2014. Ten patients underwent repair or replacement of the radial head, while thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 23 publications
0
9
1
Order By: Relevance
“…According to several studies, the treatment with a hinged external fixator is an effective supplement to open reduction and internal fixation (ORIF) to improve ligamentous and articular stability as well as the range of motion after an elbow dislocation [ 6 , 7 ]. Active and passive motion with slow stretching of the elbow during the early postoperative period is crucial in postoperative physical therapy to prevent the emergence of heterotopic ossification, which is seen in up to 75% of the cases [ 12 , 19 , 20 ]. An important determinant for a favorable clinical outcome is the compliance of the patient [ 2 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to several studies, the treatment with a hinged external fixator is an effective supplement to open reduction and internal fixation (ORIF) to improve ligamentous and articular stability as well as the range of motion after an elbow dislocation [ 6 , 7 ]. Active and passive motion with slow stretching of the elbow during the early postoperative period is crucial in postoperative physical therapy to prevent the emergence of heterotopic ossification, which is seen in up to 75% of the cases [ 12 , 19 , 20 ]. An important determinant for a favorable clinical outcome is the compliance of the patient [ 2 ].…”
Section: Resultsmentioning
confidence: 99%
“…Indications for the use of an articulated external fixator include acute instability, instability after osteosynthesis or ligamentous repair, chronic subluxation, open fractures, fracture-dislocations in uncooperative patients and complex injuries in the elderly population. We have used external fixation in patients with elbow instability, fractures and dislocations with good results, 13 and several publications have reported on the use of hinged external fixation in the treatment of both acute and chronic elbow instability. 13 Yu et al reported the outcomes of 20 cases with acute complex instability of the elbow treated with hinged external fixation.…”
Section: Discussionmentioning
confidence: 99%
“…We have used external fixation in patients with elbow instability, fractures and dislocations with good results, 13 and several publications have reported on the use of hinged external fixation in the treatment of both acute and chronic elbow instability. 13 Yu et al reported the outcomes of 20 cases with acute complex instability of the elbow treated with hinged external fixation. 14 Interestingly, these authors did not repair the LCL when using a hinged external fixator.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations